ANALYSIS OF DECISION NUMBER 26/Pid.Sus/TPK/2024/PN.Mdn CONCERNING ASSETS CONFISCATION IN AN EFFORTS TO RETURN STATE MONEY ACCORDING TO LAW NUMBER 31 Of 1999 - Indria, Tengku Dilla (Inspiring Law Journal, 2025)
Corruption is an act of abuse of power or office for personal or group interests that are contrary to law, morals or ethics. Usually corruption is carried out by public officials or parties who have authority in government, organizations or institutions to obtain financial or other benefits in an illegal manner. Asset confiscation aims to reduce the number of corruption crimes, return state losses, prevent perpetrators of corruption from enjoying the proceeds of their crimes. Corruption crimes are prosecuted at home and abroad, blocked, confiscated, transferred, and extradited to replace the financial losses of victims of corruption. Law Number 31 of 1999 concerning the Eradication of Corruption regulates legal actions that can be taken against perpetrators of corruption, including asset confiscation. Efforts to return state financial losses from perpetrators of corruption will be successful if there is cooperation between law enforcement officers (Police, Prosecutors, KPK) to uncover corruption crimes, especially in efforts to return state losses. Regarding the state financial losses, it is contained in the laws and regulations regarding criminal acts of corruption, both the old regulations, namely Law Number 3 of 1971 and the new regulations, namely Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption.